Differences in health related quality of life in the randomised ARTSCAN study; accelerated vs. conventional radiotherapy for head and neck cancer. A five year follow up. Issue 2 (February 2016) - Nyqvist, Johanna; Fransson, Per; Laurell, Göran; Hammerlid, Eva; Kjellén, Elisabeth; Franzén, Lars; Söderström, Karin; Wickart-Johansson, Gun; Friesland, Signe; Sjödin, Helena; Brun, Eva; Ask, Anders; et al.
Abstract: Background and purpose: Health related quality of life (HRQoL) was assessed in the randomised, prospective ARTSCAN study comparing conventional radiotherapy (CF) with accelerated radiotherapy (AF) for head and neck cancer. Material and methods: 750 patients with squamous cell carcinoma (of any grade and stage) in the oral cavity, oro-, or hypopharynx or larynx (except T1–2, N0 glottic carcinoma) without distant metastases were randomised to either conventional fractionation (2 Gy/day, 5 days/week in 49 days, total dose 68 Gy) or accelerated fractionation (1.1 + 2.0 Gy/day, 5 days/week in 35 days, total dose 68 Gy). HRQoL was assessed with EORTC QLQ-C30, QLQ-H&N35 and HADS at baseline, at end of radiotherapy (eRT) and at 3 and 6 months and 1, 2 and 5 years after start of treatment. Results: The AF group reported HRQoL was significantly lower at eRT and at 3 months for most symptoms, scales and functions. Few significant differences were noted between the groups at 6 months and 5 years. Scores related to functional oral intake never reached baseline. Conclusion: In comparison to CF, AF has a stronger adverse effect on HRQoL in the acute phase.